Hyponatremia in Children with Acute Lymphoblastic Leukemia - Deniz Yılmaz Karapınar; Akkız Şahin; Selime Özen; Pınar Yazıcı Özkaya; Zühal Önder Siviş; Ayşe Burcu Akıncı; Nihal Özdemir Karadaş; Bülent Karapınar (Galenos Yayinevi, 2020)
Aim:Hyponatremia is a common electrolyte abnormality in hospitalized patients. Administration of isotonic maintenance fluids is recommended to prevent hyponatremia. The present study was conducted to evaluate the frequency and severity of hyponatremia in children with acute lymphoblastic leukemia (ALL).Materials and Methods:The frequency, severity and possible causes of hyponatremia in children with ALL throughout their entire intensive treatment were retrospectively evaluated. All children in this study received isotonic fluids as maintenance IV treatment during the hospitalization period.Results:In a five-year period, 618 hyponatremia episodes seen in 92 children with ALL (median age 59 months), treated with ALLIC 2002 protocol were entered into the study. The median number of hyponatremia episodes per patient was 6. All patients had at least one hyponatremia episode of which 83.2% were classified as mild, 13.2% as moderate, 2.9% as severe and 0.6% as very severe. The median duration of hyponatremia episodes was 5 (range between 1-43) days. The total duration of all hyponatremia episodes of each patient varied from 6 to 138 days with a median of 30 days. In 241 episodes of 68 children, there was inadequate salt intake secondary to oral feeding intolerance, nausea, vomiting and oral aphthous stomatitis. In four patients, seizure was seen during the hyponatremia period and thought to be secondary to hyponatremic encephalopathy. No patient developed central pontine myelinolysis.Conclusion:Hyponatremia is very frequent in ALL patients. Despite the use of isotonic IV fluids, it seems it cannot be completely prevented.